PEMEROLEHAN BAHASA ANAK AUTIS BERDASARKAN GENDER DI SEKOLAH BINA AUTIS MANDIRI PALEMBANG - Zuraida Nfn (MEDAN MAKNA: Jurnal Ilmu Kebahasaan dan Kesastraan, 2019)
This study aims to describe the function of speech-language autistic children based on gender in school Bina Mandiri Autism Palembang and patterns of acquisition of language function is based on the types of language function developed by Halliday. The method used in this research is descriptive method. In analyzing the data used methods match those basic techniques that pragmatic aggregated power engineering and advanced engineering that appeal circuit techniques to discern. The subjects were two students Bina Mandiri Autism Palembang namely Sekar Alifia Salsabil and Jovian. The results showed that the two research subjects do not have the ability to earn a seventh language functions as proposed by Halliday. Informative function is a function of the dominant use of children with autism while the non-dominant function is the function of heuristic and imaginative function. Each function of the language used by research subjects have characteristics that mark it. Distinctive characteristics include verbal and nonverbal characteristics. When compared to the proposed acquisition of language function Halliday, the results of this study indicate that not all patterns of language acquisition functions proposed by Halliday met. In addition, new patterns are found on the instrumental function that is specific demand patterns arising from initiation are divided into normal initiation and initiation explanatory.